Verifiable multi-keyword search scheme based on improved Merkle-Tree authentication method - Youliang TIAN; Qin LUO (Tongxin xuebao)
Aiming at the problem that the result verification method in the searchable encryption scheme was complicated,the search cost was high and the efficiency was low,it was difficult to meet the requirements of efficient verification and security of multi-keyword search results,a multi-keyword search scheme based on the improved Merkle-Tree authentication method was proposed.Firstly,a multi-keyword searchable algorithm was built to achieve efficient and accurate multi-keyword search by the bilinear mapping.Secondly,based on the improved Merkle-Tree authentication method of Bawa,the verification and dynamic update algorithm of the search scheme was constructed to reduce the calculation cost of the classic MHT to prevent the efficient verification and update of illegal operations such as data tampering,deletion,and forgery.Under the decision-type linear hypothesis and CDH hypothesis,the proof scheme meets the indistinguishability and unforgeability of ciphertext.